Towards robust and replicable sex differences in the intrinsic brain function of autism - Floris, Dorothea L.; Filho, José O. A.; Lai, Meng-Chuan; Giavasis, Steve; Oldehinkel, Marianne; Mennes, Maarten; Charman, Tony; Tillmann, Julian; Dumas, Guillaume; Ecker, Christine; Dell'Acqua, Flavio; Banaschewski, Tobias; et al. (Molecular autism, 2021)
Marked sex differences in autism prevalence accentuate the need to understand the role of biological sex-related factors in autism. Efforts to unravel sex differences in the brain organization of autism have, however, been challenged by the limited availability of female data.
Gesehen am 19.08.2021